Prenatal exposure to essential metals and blood pressure at preschool age: A birth cohort study - Caifang Xu; Shiwei Jiang; Hualin Wang; Bowen Du; Qianchuo Wang; Zhuoyan Li; Zhikang Xu; Zhi Wang; Junxia Liu; Xi Zhang; Kun Sun; Jian Wang (Ecotoxicology and Environmental Safety)
Aims: To investigate the association between prenatal exposure to essential metals and the offspring blood pressure (BP) at preschool age. Materials and methods: Data from a birth cohort study including 1113 mother-child pairs were analyzed. The associations between individual prenatal essential elements and offspring BP were analyzed using generalized linear regression models. Bayesian Kernel Machine Regression (BKMR) and weighted quantile sum regression (WQS), were employed to examine the combined effects of prenatal metal exposures on offspring BP. The associations between essential metals and high blood pressure (HBP) of offspring were appraised using logistic regression model. Results: In the single-metal models, we found that maternal magnesium (Mg) concentrations were negatively associated with the offspring BP. The results of BKMR and WQS also identified a negative association between maternal essential metals mixtures and offspring BP. Logistic regression showed that compared to the highest quartiles of maternal Mg, the odds ratio (OR) for HBP in the lowest quartiles was 4.27 (95 % CI: 1.84–9.93). No significant associations were observed for other essential metals (all P value > 0.05). Additionally, no significant association was found between umbilical cord blood metal concentrations and offspring BP. Conclusions: Maternal essential metals mixtures, rather than those in umbilical cord blood, were negatively associated with offspring BP. Besides, lower maternal Mg levels were linked to a higher prevalence of HBP in offspring. Our findings provide significant evidence for exploring the effects of maternal essential metal elements on offspring BP.